Environmental Impact of Ecosystem in Angke Mangrove Nature Park from Plastic Waste - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Edelweis, Elena; Sulaiman, Angga (CV ODIS, 2023)
Mangrove forests are places where low tides come. A place that provides life for various animals, reptiles, birds to a variety of fish. Mangrove forests filter nutrients to toxins in the water, also providing protection from extreme weather. Its roots that can filter salt, breathe oxygen, and extract nutrients make mangroves able to live in salt water. The unique ability of mangrove plants is not possessed by other trees. Ecotourism or ecotourism (in English: ecotourism) is one of the environmentally friendly tourism activities by prioritise aspects of nature conservation, aspects of socio-cultural, and economic empowerment of local communities, as well as aspects of learning and education. Ecotourism began when there was a negative impact on conventional tourism activities. The impact in question is in the form of environmental damage, uncontrolled influence of local culture, reduced role of local communities, and business competition that begins to threaten the environment, culture, and economy of the local community. In collecting data types and sources, researchers collect data types in qualitative data and data sources in the form of secondary data.